Improving early literacy outcomes : curriculum, teaching, and assessment - Spaull, Nic; Comings, John P. (John Paul) (IBE on curriculum, learning, and assessment, 2019)
"Improving Early Literacy Outcomes ranges wide and deep in its search for effective ways to ensure that, by 2030, all youth, and a substantial proportion of adults, achieve literacy and numeracy, as stated in the UN Sustainable Development Goal (SDG) 4. Through probing analyses of research, policy, and practice, the book argues that improving the teaching, learning, and assessment of early grade literacy is key not only to expanding quality, access, and equity of education, but also to unlocking all the other SDGs, and ultimately to driving development. The book draws attention to the difficult challenge of catalyzing system-level change with data-proven outcomes in early grade literacy. Sixteen interlocking chapters cast an ever-vigilant and deflationary eye on the temptation to look at a single undifferentiated goal for literacy, without taking into consideration the crucial value of context"--